The Effect of Technological Gaps on Relationships Between Tourism Society with Swot Analysis in Ragunan Wildlife Park - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Rhomanhova, Zika Aqlia (CV ODIS, 2024)
As one of the favourite tourist attractions in Jakarta, Ragunan Wildlife Park needs to continue adapting to digital technology to avoid being left behind. This can affect the relationship between wildlife parks, local communities, and visitors (Dimyati, 2020). An in-depth study related to the use of digital technology in tourism public relations in Ragunan Zoo with a SWOT Analysis approach can be used to evaluate strengths, weaknesses, opportunities, and threats related to the use of technology in wildlife parks. This SWOT analysis can better understand how the technology gap affects those relationships. The type of research used is qualitative research, which is descriptive and tends to use analysis or process. The meaning is highlighted in this type of research, which emphasizes the theoretical foundation that guides research focus on the facts in the field.